Cold Sensitivity in Ulnar Neuropathy at the Elbow - Relation to Symptoms and Disability, Influence of Diabetes and Impact on Surgical Outcome - Zimmerman, Malin; Peyron, Hanna; Svensson, Ann-Marie; Eeg-Olofsson, Katarina; Nyman, Erika; Dahlin, Lars B. (Frontiers in Clinical Diabetes and Healthcare, 2021)
Cold sensitivity, an abnormal response to exposure to cold, is debilitating. It often affects persons with nerve injuries and diabetes. Knowledge about occurrence and prognostic impact of cold sensitivity in persons with ulnar nerve compression at the elbow (UNC) is limited. We aimed to investigate occurrence of cold sensitivity in UNC with its relation to disability, influence of diabetes, and impact on surgical outcome. Data concerning 1270 persons operated for UNC 2010-2016 from the Swedish National Register for Hand Surgery (HAKIR) was matched with the Swedish National Diabetes Register (NDR). Disability and symptoms were assessed preoperatively, and at three and 12 months postoperatively with QuickDASH and a symptom specific survey (HQ-8) with one item regarding cold sensitivity. Differences regarding grade of cold sensitivity, occurrence of diabetes, QuickDASH scores and HQ-8 scores were studied. A linear regression analysis was performed to predict surgical outcome based on preoperative cold sensitivity. Mean age of the cases was 52 ± SD 14 years and 48% were women. Preoperatively, 427 cases answered the questionnaire. Severe cold sensitivity was present in 140/427 (33%) cases, moderate in 164/427 (38%) and mild in 123/427 (29%) cases. Cases with severe preoperative cold sensitivity reported higher QuickDASH scores at all times compared to cases with mild cold sensitivity. Relative change in QuickDASH scores over time did not differ between the groups. Cases with diabetes reported worse cold sensitivity preoperatively, but not postoperatively. All HQ-8 items improved from surgery, but cases with severe cold sensitivity reported worse persisting symptoms. Cold sensitivity is a major problem among persons with UNC and even a larger preoperative problem among persons with diabetes. It is associated with more symptoms and disability pre- and postoperatively. All persons, regardless preoperative degree of cold sensitivity improve from surgery.